Interprofessional education experiences in the context of multiprofessional residencies in health: a review study (Research, Society and Development, 2022)
Multiprofessional Residencies in Health (RMS) have been increasingly considered as an important training alternative for health professionals for the arrangement of new techno-assistance designs. Interprofessional Health Education (IPE) occurs when two or more professions learn about, from, and with other with the common goal of improving collaboration in teamwork. It can be inserted in the context of postgraduate courses, including the RMS, aiming at the materialization of collaborative practices and the improvement of health outcomes. This study aimed to identify experiences related to IPE practices adopted in RMS scenarios at the national level. The integrative literature review method was used. Were considered studies published in Portuguese, English or Spanish, between 2010 and 2020, that dealt with IPE within the scope of RMS in Brazil. 37 studies were included and, according to their objectives, three categories were identified that characterize the scientific production on the topic: “RMS as scenarios for the promotion of the IPE and collaborative practices”, “RMS and the development of competences for work interprofessional and transformation of practices” and “Limits and challenges to IPE in RMS”. The studies found focused on analyzing the perceptions of RMS actors on IPE principles and practices; analyze institutional instruments of the RMS from the perspective of the EIP; and to describe experiences of implantation and development of activities and interprofessional practices in the RMS.